Space weather: Big & small – A continuous risk. Issue 1 (March 2019) - McIntosh, Scott W.
Abstract: "Space Weather" is the term used to describe the relentless barrage of particles that bathe the Earth and other planetary bodies of the solar system that originate in the steady evolution, and catastrophic breakdown, of magnetic structures on the Sun. The Sun literally generates the weather that populates and pervades the solar system. In our society, growing in technical dependence, the constant drip of space weather can impact ground-based infrastructure, drains satellite systems in space, presents a radiation hazard to robotic and human explorers while also protecting us from relativistic cosmic rays that penetrate from deep space, that beyond our solar system.